Comparison of Maternal and Neonatal Complications in Women with and without Gestational Diabetes Mellitus (Journal of Rangpur Medical College, 2024)
Background: Gestational Diabetes Mellitus (GDM) is a common pregnancy-related metabolic disorder associated with adverse maternal and neonatal outcomes. Gestational Diabetes Mellitus is characterized by glucose intolerance that develops during pregnancy. It affects approximately 7% of all pregnancies and has been linked to an increased risk of maternal and neonatal complications. Objective: The study was aimed to provide a comprehensive comparison of maternal and neonatal complications in women with and without GDM involving a thorough examination of medical records and clinical data to identify patterns and associations between GDM and various complications. Methods: A retrospective cohort study was conducted, including pregnant women with and without GDM who received prenatal care and underwent hospital delivery at the Department of Obstetrics and Gynecology, Enam Medical College and Hospital, Dhaka, Bangladesh from June 2022 to June 2023. Clinical data, including maternal age, gestational age at diagnosis, parity, and antenatal care were collected. Pregnancy outcomes, such as maternal complications, and live birth complications were also assessed. Result: A total of 60 pregnant women were included in the analysis, 30 were diagnosed with GDM and 30 without GDM. Analysis of pregnancy outcomes revealed a higher incidence of cesarean section deliveries in the GDM group (p